PKM MGMP Guru Matematika SMK di Kabupaten Grobogan Propinsi Jawa Tengah - Ali Shodiqin; Sugiyanti Sugiyanti; Dhian Endahwuri; Rizky Esti Utami; Muhtarom Muhtarom (Perkumpulan Kualitama Edukatika Indonesia, 2026)
The aim of this service is that teachers are willing and able to create classroom action research, compile scientific articles resulting from research in order to develop their professionalism and to form a scientific-minded mindset to support improving the quality of education. The method used to achieve this goal is with training with more demonstrations, questions and answers and practice as well as mentoring. The training material is presented with more practice than theory, with a ratio of 25% theory and 75% practice. The result of this service is an increase in the quality and quantity of professional development work in the form of reporting the results of classroom action research and scientific articles. Vocational school teachers participating in the service identify problems that are worthy of being raised as classroom action research so that the results of the research can then be made into scientific articles. Based on the results of the activities, it can be identified regarding the level of understanding that service participants can understand the concept of developing professional work, the importance of developing professional work and the importance of increasing the quality and quantity of work development in the form of reporting the results of classroom action research and scientific articles from research and about education.